Application of photogrammetry to generate quantitative geobody data in ephemeral fluvial systems. (13th November 2019) - Priddy, Charlotte L.; Pringle, Jamie K.; Clarke, Stuart M.; Pettigrew, Ross P.
Abstract: Outcrop studies are often used as analogues to subsurface sedimentary reservoirs, with photogrammetry representing a useful technique to obtain quantitative geometrical data of sedimentary architectures. Digital photogrammetric techniques were used to study fluvial sediments of the Lower Jurassic Kayenta Formation of the western USA. Model‐extracted statistics for channel and sheetflood elements, relevant to reservoir modelling, were compared with 1D and 2D datasets from the same outcrops. Results suggest that the 1D/2D data significantly underestimated element dimensions and ranges in ephemeral fluvial systems. Consequently, this study demonstrates the value of photogrammetric techniques for obtaining statistically relevant and more accurate reservoir modelling input data from outcrops. Abstract : Outcrop studies are often used as analogues to subsurface sedimentary reservoirs. Digital photogrammetric SfM‐MVS techniques were used to study fluvial sediments of the Lower Jurassic Kayenta Formation of the western USA. The resulting model‐extracted statistics for channel and sheetflood element suggest that traditional 1D and 2D datasets significantly underestimate element dimensions and ranges in ephemeral‐fluvial systems. Consequently, photogrammetric techniques provide more accurate reservoir modelling input data from outcrops. Résumé: Les études d'affleurements sont souvent utilisées pour décrire par analogie les réservoirs sédimentaires souterrains, la photogrammétrie constituant une technique utile pour obtenir des données quantitatives sur la structure sédimentaire. Des techniques de photogrammétrie numérique ont été utilisées pour étudier les sédiments fluviaux de la formation du Kayenta datant du jurassique inférieur, dans l'ouest des États‐Unis. Les statistiques extraites des modèles pour caractériser les chenaux et les nappes afin de modéliser les réservoirs ont été comparées à des données 1D et 2D sur les mêmes affleurements. Les résultats montrent que les données 1D/2D ont sous‐estimé de manière significative les dimensions des objets et les étendues des systèmes fluviaux éphémères. Cette étude démontre ainsi la valeur ajoutée des techniques photogrammétriques pour produire à partir d'affleurements des modèles de réservoirs statistiquement pertinents et plus précis. Zusammenfassung: Aufschlussstudien werden typischerweise als Analogon für Sedimentreservoirs im Untergrund verwendet. Die Photogrammetrie ist dabei eine nützliche Methode, um quantitative Daten zur Geometrie von Sedimentkörpern zu erhalten. Mittels digitaler Photogrammetrie wurden fluviale Sedimente der Kayenta‐Formation der westlichen USA untersucht. Flussrinnen‐ und Schichtfluten‐Elemente wurden aus einem Aufschlussmodell als Beispiel entnommen und statistisch ausgewertet, da diese für die Reservoir‐Modellierung von Relevanz sind. Die Ergebnisse unterstützen ein ephemeres‐fluviales Ablagerungsmodell für die Kayenta‐Formation. Ein Vergleich der durch Photogrammetrie in 3D erhaltenen Daten mit denen von Bohrkernen (1D) und Orthophotos (2D) zeigt, dass traditionelle Datenerfassungsmethoden die Größe und den Umfang von ephemeren Flusssystemen um bis zu 100 % unterschätzen. Die vorliegende Studie zeigt basierend auf Aufschlussstudien exemplarisch die Vorteile photogrammetrischer Methoden zur Bestimmung statistisch relevanter Reservoir‐Modellierungsdaten auf, die auf Sedimentreservoirs im Untergrund übertragen werden können, wo die Datenbasis meist auf eindimensionale Bohrkerninformationen beschränkt ist. Resumen: Los estudios de afloramientos se utilizan generalmente como análogos de depósitos sedimentarios subterráneos, siendo la fotogrametría una técnica útil para obtener datos cuantitativos sobre la geometría de los sedimentos. Se utilizaron técnicas de fotogrametría digital para estudiar los sedimentos fluviales de la formación Kayenta en el oeste de los Estados Unidos. Se extrajeron estadísticas de canales y elementos inundables, relevantes para el modelo, comparándose con conjuntos de datos 1D y 2D de los mismos afloramientos. Los resultados sugieren que los datos 1D/2D subestimaron significativamente las dimensiones y rango de los afloramientos fluviales efímeros. En consecuencia, este estudio demuestra la validez de las técnicas fotogramétricas para la captura de datos y modelado de afloramientos estadísticamente relevantes y precisos. 摘要: 露头通常用为研究地下储水沉积结构的观测对象, 摄影测量是获得沉积构造定量几何数据的有效技术。本研究应用数字摄影测量技术探讨美国西部下侏罗纪Kayenta构造的河流沉积物。以储水层模型相关的渠道和片材元素的模型所得统计数据, 与相同露头的一维和二维数据集进行比较。结果显示, 一维/二维数据显著低估了短暂河系的尺寸和范围。因此, 本研究证明了摄影测量技术可以应用于由露头获得统计相关的、且更准确的储水层建模输入数据。